Thermal annealing of ZnO and Al2O3 substrates - Hawrami, Banaz Muzaffar (My University, 2015)
ZnO is a compound semiconductor with a wide and direct bandgap of 3.3 eV which corresponds to UV light. This makes ZnO suitable for the violet-blue emitting optoelectronic devices. However, there are several challenges to obtain these devices. The substrate surfaces needs to be very smooth for epitaxial growth. This thesis focuses on the morphology of the Zn- and O-faces of ZnO and Al2O3 surfaces before and after thermal annealing. Several annealing parameters have been varied and the samples are analyzed by AFM and XRD. It turns out that for a high annealing temperature, the surface of Zn-face was improved. Atomic steps could observed on the surface. Smooth O-face surfaces were achieved at relatively low annealing temperatures. Sapphire is also a possible substrate for ZnO, it has also been investigated in this thesis.
Keywords: Materialvetenskap; Nanovetenskap och nanoteknik; Ytor och mellanytor; Halvledarfysik; Materials Science; Nanoscience & Nanotechnology; Surfaces and interfaces; Semiconductor physics